Modern Proposals for Improving English - Dilsuz Zoyirova Abdijalilovna; Thomas Heller (Journal of Higher Education and Academic Advancement, 2024)
In this article, the modern methods of English language teaching, which are widely used today in the higher educational institutions and legal educational institutions of our republic, are identified, fundamental, linguistic, sociocultural, and communicative methods are comparatively analyzed, and their role and importance in the educational process is shown.